Differential diagnosis of adrenocorticotropic hormone-independent Cushing syndrome: role of adrenal venous sampling. - Martins, R; Agrawal, R; Berney, D; Reznek, R; Matson, M; Grossman, AB; Druce, MR (2012)
OBJECTIVE: To outline the potential role for adrenal venous sampling in the diagnosis and management of adrenocorticotropic hormone (ACTH)-independent Cushing syndrome (CS). METHODS: We present a case description and discuss the management of a 59-year-old woman with an 8-year history of weight gain, centripetal obesity, a round plethoric face, skin thinning, easy bruising, hirsutism, and progressive muscle weakness. RESULTS: The patient reported a prior personal history of asthma, type 2 diabetes mellitus, hypertension, dyslipidemia, and bilateral leg ulcers, but she denied having any personal or family history of endocrinopathy and was not taking any corticosteroid medication. Elevated midnight serum cortisol, failure to suppress cortisol levels with a low-dose dexamethasone suppression test, and undetectable plasma ACTH all indicated ACTH-independent CS. Additional investigations including dynamic tests and adrenal imaging were supported by adrenal venous sampling in order to make a diagnosis and formulate a management plan. She was ultimately noted to have bilateral functioning adrenal nodules (adenoma and adenolipoma) and underwent successful bilateral laparoscopic adrenalectomy, with postoperative glucocorticoid and mineralocorticoid replacement. CONCLUSION: Adrenal venous sampling may be an important step in the differential diagnosis of CS and localization of the source of cortisol excess. It may distinguish pheochromocytoma or benign nonfunctioning adrenal nodules from cortisol-secreting adenomas and may avoid unnecessary bilateral adrenalectomy. It can also ensure that the correct operation is completed, if required, and thus avoid the increased morbidity and mortality associated with repeated surgical interventions.